2002
DOI: 10.1097/00004647-200205000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine Induces Delayed Tolerance against Cerebral Ischemia in Vivo and in Vitro

Abstract: The widely prescribed drug desferrioxamine is a known activator of the hypoxia-inducible transcription factor 1 (HIF-1) and the subsequent transcription of erythropoietin. In the brain, HIF-1 is a master switch of the transcriptional response to hypoxia, whereas erythropoietin is a potent neuroprotectant. The authors show that desferrioxamine dose-dependently and time-dependently induces tolerance against focal cerebral ischemia in rats and mice, and against oxygen-glucose deprivation in purified cortical neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 44 publications
7
129
0
Order By: Relevance
“…Primary neuronal cultures of cerebral cortex from rat embryos (embryonic day 18) or from PEA15 −/− mouse embryos (embryonic day 15) were dissected and cultured for up to 9 d to ensure maturation of neurons as described (19). All animal procedures were performed in accordance with the standards for animal care of our institution, and permission was obtained from the Landesamt für Gesundheit und Soziales Berlin according to the national regulations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary neuronal cultures of cerebral cortex from rat embryos (embryonic day 18) or from PEA15 −/− mouse embryos (embryonic day 15) were dissected and cultured for up to 9 d to ensure maturation of neurons as described (19). All animal procedures were performed in accordance with the standards for animal care of our institution, and permission was obtained from the Landesamt für Gesundheit und Soziales Berlin according to the national regulations.…”
Section: Methodsmentioning
confidence: 99%
“…First, we assessed whether mitochondrial hexokinases responded to a hypoxia-mimicking stimulus that activates HIF-1 transcriptional activity by interfering with degradation of HIF-1α (19). We treated cultured primary rat brain cortical neurons with the iron chelator deferoxamine (DFO), thereby mimicking hypoxia (19).…”
Section: Hif-1-dependent Activation Of Hkii In Primary Neurons and Hymentioning
confidence: 99%
“…Finally, cobalt chloride had been previously shown to act as a hypoxia mimic and it, like DFO, stabilized HIF and protected neurons from oxidative death. Moreover, in vitro and in vivo studies using DFO or cobalt chloride in several models showed dramatic neuroprotection or reductions in infarct volume by pretreatment with DFO or cobalt chloride 24 hours before stroke onset (Sharp et al, 2004;Gidday et al, 1994;Bergeron et al, 2000;Semenza, 2000;Prass et al, 2002).…”
Section: Iron Chelators: a Window Into The Hypoxic Adaptive Responsementioning
confidence: 98%
“…Whereas HIF-1␤ is constitutively expressed, the stability, DNA binding capability, and transcriptional activity of the HIF-␣ subunit are directly controlled by the intracellular oxygen concentration (9,12,32). Recent studies have demonstrated that protection of rat brain and retinal tissues by prior exposure to an episode of sublethal hypoxia is associated with elevated levels of the HIF-1␣ protein (6,7,14,30). In the neonatal rat brain HIF-1 target genes including vascular endothelial growth factor (VEGF) and Glut-1 have been shown to be upregulated by preconditioning stimulus.…”
mentioning
confidence: 99%